Women's Access to Land as Owners: Some Implications for Development Planning - Ismail, Maimunah (Universiti Putra Malaysia Press, 1993)
A study was conducted on women's access to land as owners in a district in Selangor. The study showed that women acquired land mainly through inheritances. On the other hand, in addition to inheritances, men also acquired land through government land allocation programmes and purchases. The quantitative analysis showed that older women were more likely to own land than the younger ones.Women from non-uxorilocal families had better access to land ownership than those from the uxorilocal households.